Host Susceptibility Patterns of Local Chili Varieties to Bactrocera spp. in West Sumatra: Diversity, Infestation, and Cluster Analysis - Nguyễn Phước Sang; Novri Nelly; Reflinaldon Reflinaldon; Hidrayani Hidrayani (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2026)
Fruit flies (Diptera: Tephritidae) are major pests of chili (Capsicum annuum Linnaeus) in tropical agroecosystems, but information on species dominance, infestation levels, and field susceptibility patterns of local chili varieties in West Sumatra remains limited. This study investigated Bactrocera spp. diversity, infestation levels, and varietal susceptibility patterns across four major chili-producing regencies in West Sumatra, Indonesia. Field surveys were conducted from July 2024 to March 2025 at 33 chili-growing sites in Agam, Solok, Tanah Datar, and Padang Pariaman. Fruit flies were monitored using methyl eugenol-baited modified Lynfield traps, while plant and fruit infestation were assessed through field observation and fruit dissection. Species diversity was evaluated using Shannon–Wiener, Simpson, and Pielou evenness indices. Differences in infestation among varieties were analyzed using the Kruskal–Wallis followed by Dunn’s multiple comparison test, while exploratory PCA and clustering were used to visualize infestation patterns. This study identified three fruit fly species associated with chili agroecosystems in West Sumatra, namely Bactrocera dorsalis, B. carambolae, and B. umbrosa. Among them, Bactrocera dorsalis overwhelmingly dominated the assemblages, resulting in low species diversity and evenness across regencies. Infestation levels differed among varieties, with Kuhay consistently showing the lowest plant, fruit, and overall infestation intensity. Aka, Keriting Bukittinggi, Rawit, and Kopay showed relatively higher infestation levels, although Kopay should be interpreted cautiously due to limited sample representation. These findings indicate differential field susceptibility among local chili varieties and suggest that low-infestation varieties such as Kuhay warrant further evaluation for integrated pest management and resistance-oriented breeding programs.